Epidemiology and risk factors for ESBL-producing Klebsiella pneumoniae: a case control study - Demirdag, Kutbettin; Hosoglu, Salih (J Infection Developing Countries, 2010)
Introduction: Increased production of extended-spectrum beta-lactamases (ESBLs) has become an important issue for treatment of severe Klebsiella pneumoniae (K. pneumoniae) infections. This study aimed to evaluate risk factors of infection from ESBL-producing K. pneumoniae (ESBL-KP). Methodology: Risk factors were evaluated using a retrospective case control design. Fifty-two patients admitted to Firat University Hospital (FUH) with invasive infections from ESBL-KP were employed as cases. Patients admitted to FUH with non-ESBL-producing K. pneumoniae invasive infection were chosen as controls. Potential risk factors of the cases and controls were evaluated using hospital charts. Pulsed-field Gel Electrophoresis (PFGE) was used to show the relatedness of ESBL-KP strains. Results: In univariate analysis, the following factors were found significant for ESBL-KP: pre-infection hospital stay, nosocomial origin, central venous catheterization, surgical intervention, antibiotic use longer than one week, and previous hospitalization. In contrast, stepwise logistic regression analysis showed that two variables, previous antibiotic use (p = 0.000) and surgical intervention (p = 0.006), remained significantly associated with risk for infection with an ESBL-KP. Molecular epidemiology identified several clusters among the ESBL-producing isolates. Conclusions: Antibiotic use and surgical intervention were significant associated factors for infections with ESBL-KP.
Keywords: ESBL; epidemiology; risk factors; case control study; PFGE typing